Sleep disordered breathing in Noonan syndrome: a rare case report - Marco Zaffanello; Antonia Maria Prioli; Luca Sacchetto; Emma Gasperi; Alfonso Bisceglia; Anna Ludovica Ghobert; Giorgio Piacentini (Hygeia Press di Corridori Marinella, 2018)
We report the case of a child with Noonan syndrome affected by hypertrophic cardiomyopathy and severe obstructive sleep apnea syndrome. The patient was born at 35 weeks gestational age (birth weight 3,340 g) and required mechanical ventilation. At the age of 4 years and 2 months, he was referred to our center for sleep cardiorespiratory polygraphy. His parents reported frequent obstructive sleep apnea, noisy respiration and snoring, oral breathing and falling asleep during the day. They were anxious that the child could die from asphyxiation during sleep. After the polygraph study had started, the patient began napping and immediately the polygraph showed several bouts of obstructive apnea and oxygen desaturation. He was referred for urgent adenotomy. At the age of 4 years and 5 months (3 months after surgery), the symptomatology and repeat sleep polygraph study showed a marked improvement. In conclusion, obstructive sleep apnea is a very hazardous condition for children with Noonan syndrome. They are a population at risk because of facial problems and cardiopathy. The real global incidence of obstructive sleep apnea syndrome in these children is unknown.